Medical-surgical nursing : clinical management for positive outcomes - Black, Joyce M.; Hawks, Jane Hokanson (St. Louis, Missouri : Saunders, an imprint of Elsevier Inc., 2009)
This is a comprehensive presentation of medical-surgical nursing, the nursing care of ill adults. It offers a synthesis of basic A & P, pathophysiology, medical management and nursing care.
Foundations of practice -- Foundations of medical-surgical nursing -- Physiologic functions -- Psychosocial reactions -- Musculoskeletal disorders -- Nutritional disorders -- Elimination disorders -- Sexuality and reproductive disorders -- Metabolic disorders -- Integumentary disorders -- Oxygenation disorders -- Sensory disorders -- Protective disorders --
Includes bibliographical references and index.
Keywords: SURGICAL NURSING